Oncolytic effects of parvovirus H‐1 in medulloblastoma are associated with repression of master regulators of early neurogenesis. Issue 3 (2nd September 2013) - Lacroix, Jeannine; Schlund, Franziska; Leuchs, Barbara; Adolph, Kathrin; Sturm, Dominik; Bender, Sebastian; Hielscher, Thomas; Pfister, Stefan M.; Witt, Olaf; Rommelaere, Jean; Schlehofer, Jörg R.; Witt, Hendrik
<x xml:space="preserve">Abstract</x> Based on extensive pre‐clinical studies, the oncolytic parvovirus H‐1 (H‐1PV) is currently applied to patients with recurrent glioblastoma in a phase I/IIa clinical trial (ParvOryx01, NCT01301430). Cure rates of about 40% in pediatric high‐risk medulloblastoma (MB) patients also indicate the need of new therapeutic approaches. In order to prepare a future application of oncolytic parvovirotherapy to MB, the present study preclinically evaluates the cytotoxic efficacy of H‐1PV on MB cells in vitro and characterizes cellular target genes involved in this effect. Six MB cell lines were analyzed by whole genome oligonucleotide microarrays after treatment and the results were matched to known molecular and cytogenetic risk factors. In contrast to non‐transformed infant astrocytes and neurons, in five out of six MB cell lines lytic H‐1PV infection and efficient viral replication could be demonstrated. The cytotoxic effects induced by H‐1PV were observed at LD50s below 0.05 p. f. u. per cell indicating high susceptibility. Gene expression patterns in the responsive MB cell lines allowed the identification of candidate target genes mediating the cytotoxic effects of H‐1PV. H‐1PV induced down‐regulation of key regulators of early neurogenesis shown to confer poor prognosis in MB such as ZIC1, FOXG1B, MYC, and NFIA. In MB cell lines with genomic amplification of MYC, expression of MYC was the single gene most significantly repressed after H‐1PV infection. H‐1PV virotherapy may be a promising treatment approach for MB since it targets genes of functional relevance and induces cell death at very low titers of input virus.